The Degree of Implementing the Principles of Knowledge Economic by Public School Teachers in Karak Governorate in Jordan from Principals Perspective - Al-sou'b, Ismail Mahmoud Omar (Journal of Educational and Psychological Sciences, 2021)
This study aimed to identify the degree of implementing the principles of knowledge economic by public school teachers in Karak Governorate from the principal's perspective. To achieve the objectives of the study, the researcher used the descriptive analysis approach, the sample of the study consisted of (82) female and male principals, and a questionnaire for data collection; consisted of (35) statements, distributed for five sectors. The results indicated that the degree of implementing the principles of knowledge economic by public school teachers in Karak Governorate from the principal's perspective was moderated with average (3.63 out of 5), the sector of "teaching strategies" was high with an average (3.89), then the sector of " evaluating" was moderated with average (3.67) then the sector of" teaching technology" was also moderated with average (3.65) then the sector of "student" was moderated with an average of (3.59) finally the sector of " teacher" with average (3.36) also was moderated. furthermore, there were no statistically significant differences at (α ≤ 0.05) in the variable of principals' sex. However, there were statistically significant differences due to the qualification of the participants in favor of (High studies). Based on the results, the researcher presented a number of recommendations and proposals, to enhance the implementation of knowledge economic principles in public schools in Karak, and the whole of the Kingdom and the Arab countries.
Keywords: Degree of Implemanting Principles of Knowledge Economic; Opinion of Principals School; Karak Governorate; Jordan